Informasi Analisis Kebutuhan Ruang Parkir Pada Area Wisata Religi Kadilangu Demak - Zaim, Mohamad Zaim; Khotibul Umam; Ariyanto (Jurnal Civil Engineering Study, 2025)
Kadilangu is one of the famous religious tourism destinations in Demak, Central Java. This high number of visitors leads to the need for adequate supporting facilities, including adequate parking areas. With the increase in the number of visitors, the problem of limited parking space began to become a major concern. This condition often causes traffic congestion, visitor inconvenience, and a decrease in the quality of the tourist experience. The design methodology is a series or frame of mind in the parking lot design process, the data analysis method is used to plan by utilizing knowledge and analyzing the behavior of the subjects involved. Generally, the data obtained through this method is in the form of interviews or questionnaires, so the results produced are more often in the form of numbers. Based on the data analysis carried out, it can be known the available static capacity and the need for parking space. If the need for parking space is greater than the available capacity, it means that the number of available parking spaces is not enough. On the other hand, if the need for parking space is smaller than the available capacity, it means that the number of available parking spaces is still able to accommodate vehicles that will be parked. From the results of the analysis, it was found that the parking space of Kadilangu Demak was able to meet the demand for the required parking space, with the note that the maximum number of parked vehicles was still below the value of the available static capacity.